Impact of Self-Esteem on the Academic Performance of the Selected Grade 12 Humanities and Social Sciences Students at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Self-esteem is a common problem in many countries, especially those affected by thepandemic. It is characterized by a lack of confidence and can make it difficult for students toconcentrate and take risks. This study looks at the causes of low self-esteem and its effects onstudents. Education is an important aspect of human resource development. Poor academicperformance has a negative impact on both the child's self-esteem and the parents.Table 2 showed that the gender of the respondents was female, with 82% being female and18% being male. Table 6 presented the mean of 2.57 as interpreted as a Great extent inSocializing, 2.55 as interpreted as Motivation, and 2.25 as interpreted as a Low extent. Theoverall weighted mean is 2.46. This study found that the majority of respondents werebetween the ages of 16 and 18 years old, with 82% female. It also found that 2.57 percent ofstudents feel that Socialization has an impact on their academic performance.The researchers concluded that the outcome of the study is solely based on the facts and thatthe related Challenges of having low self-esteem in their academic performance areoutweighed by having a 2.94. The researchers recommend this study to any student who isinterested in dealing with this type of problem and is looking for a solution.
Keywords: Education